The realisation of an electro-Optical Diffraction Grating using HeNe laser - Abdulsattar A. Aesa; C.D. Walton (Tikrit Journal of Pure Science)
This paper reports far-field of the electro-optical diffraction grating to the advantage of electro-optic response of 5CB liquid crystal. The diffraction grating was produced by intersacting of two laser beam of laser HeNe 632.8nm wavelength radiation transmitted through a 5CB liquid crystal dopped Sudan Black B (SBB) dye in a cell with a thickness of 5µm and applying a uniform electric filed across the cell.  Different concentrations of SBB dye were prepared and optically characterised. Double side tape in a thickness of 5 µm was used to determine the cell thickness. Zero and two diffraction orders were observed. 16 µm grating period involve in a produced electro-optical diffraction grating. The effect of changing voltage was investigated. The possibility of realising the electro-optical diffraction grating made of 5CB liquid crystal doped biocompatible material chitosan doped SBB dye to enhance the absorption properties were also investigated and characterised using Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), UV-vis spectrophotometer and optical microscope. A fabricated Electro-Optic diffraction grating was experimentally characterized. Applications of liquid crystal and the electro-optic effect were discussed briefly.